TransArea A Literary History of Globalization - Ette, Ottmar (De Gruyter, 2016)
The future of area studies lies in opening out into TransArea studies, which tie together area-connected competencies with transdisciplinary research practices. It is one of the loftiest and most urgent duties of philology to lift up this treasure in the awareness of the special relevance of literature, and to make it democratically available to the broadest possible sections of the population.